Is it wrong to try to pick up girls in a dungeon? On the side. Sword oratoria. 17 - Ōmori, Fujino; Yagi, Takashi (Yen Press, 2022)
"Looking for the key to the man-made dungeon Knossos, Bete ends up going on a date with the Amazon Lena, who has a one-sided crush on him. While he succeeds in getting information from Lena, as the two of them look for the key, they are set upon by a group of assassins! Their fiercest enemy, Valleta, stands in their way, and she's not going down without a fight!"--